MEDB-42. GermlineElp1 deficiency promotes genomic instability and survival of granule neuron progenitors primed for SHH medulloblastoma pathogenesis. (3rd June 2022) - Garcia-Lopez *, Jesus; Ahmad *, Shiekh Tanveer; Li *, Yiran; Gudenas, Brian; Kojic, Marija; Manz, Friedrik; Jonchere, Barbara; Mayasundari, Anand; Pitre, Aaron; Hadley, Jennifer; Paul, Leena; Batts, Melissa; et al.
Abstract: Germline loss-of-function (LOF) mutations in Elongator complex protein 1 (ELP1 ) are found in 15-20% of childhood SHH medulloblastoma (MB) and are exceedingly rare in non-SHH-MB or other cancers. ELP1 germline carriers that develop SHH-MB harbor frequent somatic PTCH1 mutations and universally sustain loss-of-heterozygosity of the remaining ELP1 allele through chromosome 9q deletion. ELP1 functions as a scaffolding subunit of the Elongator complex that is required for posttranscriptional modification of tRNAs and maintenance of efficient translational elongation and protein homeostasis. However, the molecular, biochemical, and cellular mechanisms by which ELP1/Elongator LOF contribute to SHH-MB tumorigenesis remain largely unknown. Herein, we report that mice harboring germline Elp1 monoallelic loss (i.e., Elp1 +/ - ) exhibit hallmark features of malignant predisposition in developing cerebellar granule neuron progenitors (GNPs), the lineage-of-origin for SHH-MB. Elp1 +/ - GNPs are characterized by increased replication stress-induced DNA damage, upregulation of the homologous recombination repair pathway, aberrant cell cycle, and attenuation of p53-dependent apoptosis. CRISPR/Cas9-mediated Elp1 and Ptch1 gene targeting in mouse GNPs reproduces highly penetrant SHH-MB tumors recapitulating the molecular and phenotypic features of patient tumors. Reactivation of the p53 pathway through MDM2 and PAK4 inhibitors promotes selective cell death in patient-derived xenograft tumors (PDX) harboring deleterious ELP1 mutations. Together, our findings reveal that germline Elp1 deficiency heightens genomic instability and survival in GNPs, providing a mechanistic model for the subgroup-restricted pattern of predisposition and malignancy associated with pathogenic ELP1 germline carriers. These results provide rationale for further preclinical studies evaluating drugs that overcome p53 pathway inhibition in ELP1 -associated SHH-MB and a renewed outlook for improving treatment options for affected children and their families.*, # Contributed equally